Retinal Optical Coherence Tomography Angiography Parameters Between Patients With Different Causes of Chronic Kidney Disease - Yong, Meng Hsien; Ong, Ming Yean; Tan, Kuan Sze; Hussein, Siti Husna; Mohd Zain, Ayesha; Mohd, Rozita; Mustafar, Ruslinda; Wan Abdul Halim, Wan Haslina (Frontiers in Cellular Neuroscience, 2022)
Background Chronic kidney disease (CKD) is a major public health issue because of the rising number of patients with the risk of progression to end-stage renal disease. The retinal micro-vasculatures provide a unique window to assess systemic microcirculation. Optical Coherence Tomography Angiography (OCTA) parameters may provide a non-invasive method for systemic correlation. This research aims to compare the association of OCTA parameters in different causes of CKD. Methods This is a single-center cross-sectional study on patients with CKD at the Universiti Kebangsaan Malaysia Medical Centre over 2 years. Patients with CKD were divided into three groups: DM group (diabetic CKD), HPT group (hypertensive CKD), and AG group (autoimmune-related glomerulonephritis CKD). The OCTA parameters, namely, the foveal avascular zone (FAZ), vascular density (VD), perfusion density (PD), and macular volume (MV), were measured and recorded using OCTA. Blood and urine analyses were taken as the patient’s CKD profile. The demographic data, the OCTA parameters and the CKD profiles, were analyzed using SPSS version 23. Results The right eyes of 232 patients were included. The median age of the control and CKD subjects were 36 and 61 years old respectively. The proportion of the subjects under the control, diabetes mellitus (DM), HPT, and AG group were 30.6, 53.4, 5.6, and 10.4% respectively. There was no significant difference in FAZ, but there is a significant difference in the VD, PD, and MV between the control and CKD groups. There was a statistically significant difference between the three different causes of CKD in VD and PD (p < 0.001, p = 0.001, respectively). When compared with the control group for VD and PD, there were significant differences between the DM-control group (p < 0.001, p < 0.001) even when the age variable was considered, but no significant difference when comparing the HPT-control and the AG-control. There was a significant correlation between age, FBS, and HbA1c with VD and PD. There was no significant association between CKD profile and FAZ. Conclusion Our study showed the meaningful reduction of VD and PD in patients with diabetes and CKD. However, the use of OCTA to screen or predict CKD in patients living with diabetes mellitus, hypertension, or autoimmune nephritis was not shown to be useful.